High-strength phosphogypsum aggregate and preparation method thereof

By using a shell material to wrap the core material in phosphogypsum aggregate, the problem of softening of phosphogypsum building materials in a humid environment is solved, and the compressive strength of the aggregate is improved to meet the strength requirements in structural engineering.

CN119330624APending Publication Date: 2025-01-21GUIZHOU POLYTECHNIC COLLEGE OF COMM

Patent Information

Application Number
CN202411543435.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing phosphogypsum building materials are prone to softening in humid or watery environments, resulting in limited application in structural engineering, and the compressive strength of the core material is not sufficient to meet the needs of C20~C60 concrete.

Method used

The structural design uses shell material to wrap the core material. The core material is composed of phosphogypsum powder, admixtures and water. The shell material uses Portland cement and sulfoaluminate cement. The strength of the aggregate is improved through specific proportions and processing methods. .

Benefits of technology

It has achieved high-strength phosphogypsum aggregate with high strength in both the core and outer shell. The compressive strength reaches 30~40MPa, which meets the strength requirements of C20~C60 concrete and has advantages in cost control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330624A_ABST
    Figure CN119330624A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building material preparation, and discloses a high-strength ardealite aggregate and a preparation method thereof. The aggregate comprises the following components: the aggregate is prepared by wrapping an inner core material with a shell material; wherein the core material comprises ardealite powder, an additive and water, and the shell material is obtained by mixing Portland cement and sulphoaluminate cement according to a ratio of (70-90): (10-30). The ratio of the ardealite powder to the water is 1: (0.28-0.35); the admixture comprises a water reducing agent and a retarder, the addition amount of the water reducing agent accounts for 0.50%-1.50% of the phosphogypsum powder, and the addition amount of the retarder accounts for 0.05%-0.10% of the phosphogypsum powder. The high-strength ardealite aggregate disclosed by the invention has a double-hard characteristic, the inner core and the shell both have relatively high strength, and the high-strength ardealite aggregate can be used for preparing C20-C60 concrete. The inner core of the aggregate is compact ardealite slurry formed by the additive, and different from extrusion forming of traditional unfired aggregate production, the high-strength aggregate with the size being 5 mm or below can be produced, and the defect of gradation is made up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material preparation, in particular to a high-strength phosphogypsum aggregate and a preparation method of the aggregate. Background Art

[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process, and its main component is calcium sulfate dihydrate. The composition of phosphogypsum is relatively complex. In addition to calcium sulfate, there are also incompletely decomposed phosphate ore, residual phosphoric acid, fluoride, acid insoluble matter, organic matter, etc. Among them, the presence of fluorine and organic matter has the greatest impact on the resource utilization of phosphogypsum. The random discharge and accumulation of phosphogypsum has seriously damaged the ecological environment, not only polluting groundwater resources, but also causing waste of land resources. How to make good use of phosphogypsum and turn waste into treasure has become the focus of research and application related to phosphogypsum.

[0003] Processing phosphogypsum into phosphogypsum powder, and then making it into new building materials such as plaster mortar, blocks, strips, and gypsum boards, has been widely used in the market. The problem is that phosphogypsum building materials are mostly used indoors and rarely used outdoors. The main reason is that gypsum building materials are air-hardening cementitious materials, which will soften in a humid and wet environment. The problem caused by the restriction of the use of engineering parts is that the amount of gypsum consumed is insufficient, and it is difficult to achieve a "production and consumption balance" with the newly produced phosphogypsum each year. In order to improve the application of phosphogypsum in the engineering field, it is necessary to solve the use of phosphogypsum in a humid and wet environment. The more mature technology is to make phosphogypsum into lightweight aggregate and prepare it into concrete or inorganic binder for use in the engineering field.

[0004] The patent with reference number CN115677306B discloses a green artificial aggregate based on phosphogypsum and its preparation method. The aggregate prepared with 10-80 parts of phosphogypsum, 10-80 parts of waste incineration ash and 10 parts of cement clinker has a compressive strength of 2.0-2.9MPa. The patent with reference number CN116621482A discloses a high-density phosphogypsum-based aggregate and its preparation method and application. It uses three sets of roller devices to repeatedly extrude and shape to prepare granular aggregate. The patent with reference number CN115611539A discloses a recycled aggregate, roadbed material and its preparation method prepared by using steel slag and phosphogypsum. It uses steel slag powder to modify the phosphogypsum and forms it in a ball-forming plate. The produced aggregate is mainly used for roadbed materials. Combined with the analysis of the above-mentioned patents, it can be seen that the technical route of using gypsum or other types of industrial waste to make lightweight aggregate in existing research is to mix industrial waste, cement, lime and water into granular materials, modify the waste using alkaline materials such as cement and lime, and then coat the granular materials with cement in a ball-forming plate to finally form lightweight aggregate with a hard outer shell and a soft inner core.

[0005] However, the compressive strength of the core material is less than 10MPa, and the cylinder compressive strength after molding is less than 3.5MPa, which cannot meet the preparation requirements of C20~C60 concrete in existing structural engineering. In order to improve the strength of aggregate, the double-roll extrusion method is used to densify and strengthen the aggregate. However, this method can generally produce aggregates larger than 10mm, but aggregates smaller than 10mm are not suitable for production. Summary of the invention

[0006] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a high-strength phosphogypsum aggregate and a preparation method thereof to improve the strength of the inner core of the gypsum-based aggregate, and to develop a high-strength phosphogypsum-based aggregate with dual hardness of the inner core and the outer shell to meet the strength requirements of structural engineering concrete for aggregates.

[0007] A high-strength phosphogypsum aggregate, characterized in that the aggregate has the following components: the aggregate is obtained by wrapping a core material with a shell material; wherein the core material includes phosphogypsum powder, an admixture and water, and the shell material is at least one of silicate cement and sulphoaluminate cement.

[0008] As a further improvement of the above scheme, the ratio of the phosphogypsum powder to water is 1:0.28~0.35; the admixture includes a water reducer and a retarder, wherein the amount of the water reducer added accounts for 0.50%~1.50% of the phosphogypsum powder, and the amount of the retarder added accounts for 0.05%~0.10% of the phosphogypsum powder.

[0009] As a further improvement of the above scheme, the ratio of the phosphogypsum powder to water is 1:0.28, the amount of the water reducer added accounts for 1.50% of the phosphogypsum powder, and the amount of the retarder added accounts for 0.10% of the phosphogypsum powder.

[0010] As a further improvement of the above scheme, the water reducing agent is any one of polycarboxylic acid water reducing agent, sulfonated melamine high efficiency water reducing agent and naphthalene high efficiency water reducing agent. In the present invention, the water reducing agent is added to reduce the amount of mixing water while maintaining the slump of concrete substantially unchanged, and the water reduction rate is above 15%.

[0011] As a further improvement of the above scheme, the retarder is at least one of a protein gypsum-based retarder, citric acid, sodium citrate, tartaric acid and potassium tartrate. In the present invention, the retarder is added to delay the hydration reaction, thereby extending the setting time of the concrete, allowing the fresh concrete to maintain plasticity for a longer time, facilitating pouring and improving construction efficiency.

[0012] As a further improvement of the above scheme, when the shell material is made of silicate cement and sulphoaluminate cement, the silicate cement and sulphoaluminate cement are mixed in a ratio of 70-90:10-30 to obtain the shell material.

[0013] A method for preparing aggregate, which is used to prepare the high-strength phosphogypsum aggregate, comprises the following steps:

[0014] S1: taking phosphogypsum powder, admixture and water, stirring and mixing to form a flowing slurry;

[0015] S2 passes the slurry through a screen to form a thin bundle;

[0016] S3 The thin bundle-like slurry enters a horizontal mixer filled with shell materials, the thin bundle-like slurry is broken, and the shell materials adhere to the broken slurry to obtain particles;

[0017] S4: screening the materials in the horizontal mixer, and forming the screened particles to obtain aggregate.

[0018] As a further improvement of the above solution, the fluidity of the slurry is not less than 200 mm. In the present invention, the fluidity is used to measure the flow performance of the slurry to ensure that the prepared aggregate meets the strength requirements in concrete structure engineering.

[0019] As a further improvement of the above scheme, the mesh size of the screen is 0.63mm, 1.25mm, 2.50mm, 5.00mm, 10.00mm, 16.00mm or 20.00mm. In the present invention, the slurry is in a thin bundle shape through the screen, so as to achieve the purpose of controlling the particle size of the aggregate, and it is convenient to produce aggregate with a particle size of no more than 20mm. In addition, since the slurry forms a thin bundle after being screened, when the shell material is subsequently mixed and wrapped, the shell formed is thinner, which is convenient to control the cost.

[0020] As a further improvement of the above scheme, the rotation speed of the horizontal mixer is 30-60 r / min; the thin bundles of slurry are broken, and the shell material is adhered to the broken slurry, and the shell material forms particles after hardening.

[0021] As a further improvement of the above scheme, the material in the horizontal mixer is screened, the particles are separated from the excess shell material, and the screened particles are put into a ball-forming plate and rolled to form spherical aggregate. In the present invention, the particle size of the spherical aggregate is positively correlated with the specification of the screen used in S2, that is, the larger the size of the screen hole, the larger the aggregate obtained. Based on this, in actual production, adaptive production can be performed to obtain aggregate of the target particle size.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention makes full use of the rapid strength development of phosphogypsum in the early stage and can form a slurry with relatively thick but good fluidity under the condition of low water-binder ratio. The strength of the slurry after hardening can reach 30-40MPa, thereby improving the core strength.

[0024] Compared with the production of traditional unfired lightweight aggregate, the high-strength phosphogypsum aggregate produced by the present invention has dual-hard characteristics, with both the inner core and the outer shell having higher strength, which is different from the traditional soft core and hard shell structure. Therefore, the high-strength phosphogypsum-based aggregate produced by the present invention can be used for C20~C60 concrete.

[0025] Compared with the production of traditional unfired lightweight aggregate, the core material of the high-strength phosphogypsum aggregate produced by the present invention is a dense phosphogypsum slurry formed by an admixture. Different from the extrusion molding of the traditional production of unfired aggregate, this method can produce high-strength aggregate below 5 mm, making up for the lack of grading. At the same time, due to the small amount of water in the slurry, the fine bundles formed by the screen are not easy to stick together, and the shell formed when it is wrapped with the outer shell material in the mixer is also thin, which is convenient for controlling costs. The size of the aggregate particle size is controlled by adjusting the size of the screen aperture, so that aggregate with a particle size not greater than 20 mm can be produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Shown is a flow chart of a method for preparing aggregate provided by the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.

[0028] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0029] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values ​​and all integers and fractions within the range.

[0030] The specific embodiments of the present invention are described in detail below.

[0031] Example 1

[0032] The present embodiment provides a high-strength phosphogypsum aggregate, which has the following components: the aggregate is obtained by wrapping a core material with a shell material. The core material includes phosphogypsum powder, an admixture and water, and the ratio of the phosphogypsum powder to water is 1:0.28; the admixture includes a polycarboxylic acid water reducer and a protein gypsum-based retarder, wherein the amount of the polycarboxylic acid water reducer added accounts for 1.50% of the phosphogypsum powder, and the amount of the protein gypsum-based retarder added accounts for 0.10% of the phosphogypsum powder. This embodiment uses phosphogypsum powder as an example for illustration. In other embodiments, high-strength gypsum powder and anhydrous gypsum powder that can meet the requirements of "Building Gypsum" GB / T9776 can also be used instead.

[0033] The shell material is obtained by mixing silicate cement and sulphoaluminate cement in a ratio of 70:30.

[0034] The preparation method of the protein-based gypsum retarder of the present embodiment comprises the following steps:

[0035] S1: Take phosphogypsum powder, polycarboxylate water reducer, protein gypsum-based retarder and water, stir and mix to form a flowing slurry with a fluidity of 210 mm.

[0036] S2 passes the slurry through a sieve with a mesh size of 10.00 mm to form a thin bundle.

[0037] S3 thin beam slurry enters into a horizontal mixer filled with shell material, the rotation speed of the horizontal mixer is 30~60r / min, the thin beam slurry is broken, the shell material adheres to the broken slurry, and the shell material hardens to form particles.

[0038] S4 sieves the material in the horizontal mixer to separate the particles from the excess shell material, and the sieved particles are put into a ball-forming plate and rolled to form spherical aggregates with a particle size of 10.00 mm.

[0039] Example 2

[0040] The present embodiment provides a high-strength phosphogypsum aggregate, which has the following components: the aggregate is obtained by wrapping a core material with a shell material. The core material includes phosphogypsum powder, an admixture and water, the ratio of the phosphogypsum powder to water is 1:0.30, the admixture includes a sulfonated melamine-based high-efficiency water reducer and sodium citrate, the amount of the sulfonated melamine-based high-efficiency water reducer added accounts for 1.20% of the phosphogypsum powder, and the amount of sodium citrate added accounts for 0.08% of the phosphogypsum powder. The present embodiment takes phosphogypsum powder as an example for illustration. In other embodiments, high-strength gypsum powder and anhydrous gypsum powder that can meet the requirements of "Building Gypsum" GB / T9776 can also be used instead.

[0041] The shell material is obtained by mixing silicate cement and sulphoaluminate cement in a ratio of 80:20.

[0042] The preparation method of the protein-based gypsum retarder of the present embodiment comprises the following steps:

[0043] S1: Take phosphogypsum powder, sulfonated melamine high-efficiency water reducing agent, sodium citrate and water, stir and mix to form a flowing slurry, the fluidity of the slurry is 220mm.

[0044] S2 passes the slurry through a sieve with a mesh size of 5.00 mm to form a thin bundle.

[0045] S3 thin beam slurry enters into a horizontal mixer filled with shell material, the rotation speed of the horizontal mixer is 30~60r / min, the thin beam slurry is broken, the shell material adheres to the broken slurry, and the shell material hardens to form particles.

[0046] S4 sieves the material in the horizontal mixer to separate the particles from the excess shell material, and the sieved particles are put into a ball-forming plate and rolled to form spherical aggregates with a particle size of 5.00 mm.

[0047] Example 3

[0048] The present embodiment provides a high-strength phosphogypsum aggregate, which has the following components: the aggregate is obtained by wrapping a core material with a shell material. The core material includes phosphogypsum powder, an admixture and water, the ratio of the phosphogypsum powder to water is 1:0.35, the admixture includes a naphthalene-based high-efficiency water reducer and potassium tartrate, the amount of the naphthalene-based high-efficiency water reducer added accounts for 1.10% of the phosphogypsum powder, and the amount of potassium tartrate added accounts for 0.09% of the phosphogypsum powder. The present embodiment takes phosphogypsum powder as an example for illustration. In other embodiments, high-strength gypsum powder and anhydrous gypsum powder that can meet the requirements of "Building Gypsum" GB / T9776 can also be used instead.

[0049] The shell material is obtained by mixing silicate cement and sulphoaluminate cement in a ratio of 90:10.

[0050] The preparation method of the protein-based gypsum retarder of the present embodiment comprises the following steps:

[0051] S1: Take phosphogypsum powder, naphthalene-based high-efficiency water reducer, potassium tartrate and water, stir and mix to form a flowing slurry with a fluidity of 230 mm.

[0052] S2 passes the slurry through a sieve with a mesh size of 2.50 mm to form a thin bundle.

[0053] S3 thin beam slurry enters into a horizontal mixer filled with shell material, the rotation speed of the horizontal mixer is 30~60r / min, the thin beam slurry is broken, the shell material adheres to the broken slurry, and the shell material hardens to form particles.

[0054] S4 sieves the material in the horizontal mixer to separate the particles from the excess shell material, and the sieved particles are put into a ball-forming plate and rolled to form spherical aggregates with a particle size of 2.50 mm.

[0055] The compressive strength test was performed on the aggregates of Example 1, Example 2 and Example 3. The specific test process is not repeated here. The test results show that the compressive strength of the aggregate parent materials of Examples 1 to 3 all reach above 30 MPa. The aggregates of Example 1, Example 2 and Example 3 were used respectively to prepare concrete after seven days of natural curing. The compressive strength test was also performed on the concrete. The test results show that the compressive strength of the concrete can reach 60 MPa. The above results prove that the high-strength phosphogypsum aggregate of the present invention can be used to prepare C20~C60 concrete to meet the needs of construction projects.

[0056] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.

Claims

1. A high-strength phosphogypsum aggregate, characterized in that: The aggregate has the following components: the aggregate is obtained by wrapping a core material with a shell material; wherein the core material includes phosphogypsum powder, an admixture and water, and the shell material is at least one of silicate cement and sulphoaluminate cement.

2. The high-strength phosphogypsum aggregate according to claim 1, characterized in that: The ratio of the phosphogypsum powder to water is 1:0.28~0.35; the admixtures include a water reducer and a retarder, wherein the amount of the water reducer added accounts for 0.50%~1.50% of the phosphogypsum powder, and the amount of the retarder added accounts for 0.05%~0.10% of the phosphogypsum powder.

3. The high-strength phosphogypsum aggregate according to claim 2, characterized in that: The ratio of the phosphogypsum powder to water is 1:0.28, the amount of the water reducer added accounts for 1.50% of the phosphogypsum powder, and the amount of the retarder added accounts for 0.10% of the phosphogypsum powder.

4. The high-strength phosphogypsum aggregate according to claim 3, characterized in that: The water reducer is any one of a polycarboxylate water reducer, a sulfonated melamine-based high-efficiency water reducer, and a naphthalene-based high-efficiency water reducer; The retarder is at least one of a protein-based gypsum retarder, citric acid, sodium citrate, tartaric acid and potassium tartrate.

5. The high-strength phosphogypsum aggregate according to claim 4, characterized in that: When the shell material is silicate cement and sulphoaluminate cement, silicate cement and sulphoaluminate cement are mixed in a ratio of 70-90:10-30 to obtain the shell material.

6. A method for preparing aggregate, which is used to produce the high-strength phosphogypsum aggregate as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1: taking phosphogypsum powder, admixture and water, stirring and mixing to form a flowing slurry; S2 passes the slurry through a screen to form a thin bundle; S3 The thin bundle-like slurry enters a horizontal mixer filled with shell materials, the thin bundle-like slurry is broken, and the shell materials adhere to the broken slurry to obtain particles; S4: screening the materials in the horizontal mixer, and forming the screened particles to obtain aggregate.

7. The method for preparing aggregate according to claim 6, characterized in that: The fluidity of the slurry is not less than 200 mm.

8. The method for preparing aggregate according to claim 7, characterized in that: The mesh size of the sieve is 0.63 mm, 1.25 mm, 2.50 mm, 5.00 mm, 10.00 mm, 16.00 mm or 20.00 mm.

9. The method for preparing aggregate according to claim 8, characterized in that: The rotating speed of the horizontal mixer is 30-60 r / min; The thin bundles of pulp are broken, and the shell material is attached to the broken pulp, and the shell material hardens to form particles.

10. The method for preparing aggregate according to claim 9, characterized in that: The materials in the horizontal mixer are screened, the particles are separated from the excess shell material, and the screened particles are put into a ball-forming plate and rolled to form spherical aggregates.

Citation Information

Patent Citations

  • Recycled aggregate prepared from steel slag and phosphogypsum, roadbed material and preparation method thereof

    CN115611539A

  • A green artificial aggregate based on phosphogypsum and preparation method thereof

    CN115677306B

  • High-density ardealite-based aggregate as well as preparation method and application thereof

    CN116621482A

Cited By

  • Phosphogypsum framework material inclusion and preparation method thereof

    CN121494483A

  • A phosphogypsum skeleton material package and a preparation method thereof

    CN121494483B